2022
DOI: 10.1002/andp.202200263
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Band Chiral Nonlinear Metasurface Supported by Quasibound States in the Continuum

Abstract: This paper presents an all-dielectric chiral metasurface composed of an array of two-layer distorted square structures with nanoholes. This metasurface can simultaneously generate dual-band opposite chiral responses, which can be attributed to the bound states in the continuum (BICs) and the distorted chiral structure. By combining the BICs with chirality, a dual-band chiral nonlinear metasurface and a chiral-sensing method are proposed. The simulated results show that the third harmonic generation (THG) conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The authors demonstrated numerically that such structures can achieve near-unity TH CD in the vicinity of the quasi-BIC mode together with the enhancement of the overall TH signal. This concept was later applied to double-layer photonic crystal slabs with asymmetric dimer-shaped holes in Si film 89 …”
Section: Metasurfaces With Bicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated numerically that such structures can achieve near-unity TH CD in the vicinity of the quasi-BIC mode together with the enhancement of the overall TH signal. This concept was later applied to double-layer photonic crystal slabs with asymmetric dimer-shaped holes in Si film 89 …”
Section: Metasurfaces With Bicsmentioning
confidence: 99%
“…This concept was later applied to double-layer photonic crystal slabs with asymmetric dimer-shaped holes in Si film. 89 The pioneering experimental observations of chiral nonlinear BICs for strong nonlinear CD have been reported only recently. 46,90 Shi et al 46 studied an Si metasurface composed of a square lattice of asymmetric meta-atoms, with the schematic and SEM images shown in the top and bottom left panels of Fig.…”
Section: Metasurfaces With Bicsmentioning
confidence: 99%
“…Meanwhile, the twisted metasurface system composed of a series of stacked identical metasurfaces arranged with a rotation angle can exhibit evident optical chirality [39]. Consequently, empowered by quasi-BICs, a stacked metasurface system with a pair of twisted metasurfaces have been proposed to achieve spectrum selective chirality at a single wavelength [40,41], two wavelengths [42] or multi wavelengths [43]. However, the chirality of these metasurfaces at these resonant wavelengths cannot be independently controlled by adjusting the structural parameters.…”
Section: Introductionmentioning
confidence: 99%